Pelatihan Jaringan Berbasis Mikrotik Untuk Peningkatan Kompetensi Siswa kelas XI di SMKN 1 Pringgasela - Amri Muliawan Nur; Hariman Bahtiar; Yahya; Nurhidayati; Almi Yulistia Alwanda; Amir Bagja (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
Computer networks are one of the important subjects in the field of information technology. Various types of computer network devices continue to innovate to adapt to technological developments. Mikrotik is one of the router products that is widely used to implement a network system. As an educator, in this case a lecturer is required to implement the Tri Darma every year, one of which is PKM, namely Community Service, which this year is focused on the Computer Department at SMKN 1 Peringgasela. The aim of this training is to increase understanding and competence in the field of computer networks using Mikrotik, and to prepare students to face the Skills Competency Examination (UKK) as well as providing preparation for the implementation of the PSG and when they graduate. The training methods used are lectures and practice (Demostration). The results of this training activity in general, apart from the enthusiasm and enthusiasm of the students, include several components, namely: 1) Success in training, 2) Achievement of planned research objectives, 3) Achievement of planned material targets